2020
DOI: 10.3390/s20030765
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Atrial Fibrillation Episodes in Long-Term Heart Rhythm Signals Using a Support Vector Machine

Abstract: Atrial fibrillation (AF) is a serious heart arrhythmia leading to a significant increase of the risk for occurrence of ischemic stroke. Clinically, the AF episode is recognized in an electrocardiogram. However, detection of asymptomatic AF, which requires a long-term monitoring, is more efficient when based on irregularity of beat-to-beat intervals estimated by the heart rate (HR) features. Automated classification of heartbeats into AF and non-AF by means of the Lagrangian Support Vector Machine has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 68 publications
(131 reference statements)
0
17
0
Order By: Relevance
“…The SVM classifier is a widely applied method of classification for biomedical signals [ 62 , 63 , 64 , 65 ] due to its excellent generalization capability. It obtains the optimal separating hyperplane for class separation by converting input features to higher dimensions through some nonlinear mapping [ 66 ]. The distance between patterns and the hyperplane is maximized using a maximum margin principle to get the best separation.…”
Section: Methodsmentioning
confidence: 99%
“…The SVM classifier is a widely applied method of classification for biomedical signals [ 62 , 63 , 64 , 65 ] due to its excellent generalization capability. It obtains the optimal separating hyperplane for class separation by converting input features to higher dimensions through some nonlinear mapping [ 66 ]. The distance between patterns and the hyperplane is maximized using a maximum margin principle to get the best separation.…”
Section: Methodsmentioning
confidence: 99%
“…variability of RR intervals) and/or morphological (i.e. absence or irregularity of P-wave) properties of the ECG signal [66][67][68][69]. It has been recently shown that atrial fibrillation episodes can be detected using features derived from beat-to-beat interval based on PPG signal as an alternative to existing ECG based solutions, where various features (such as the normalized root mean square of successive differences (RMSSD), sample entropy, etc.)…”
Section: B Heart Rate Preservation In Generated Ppg and Potential Applications To Data Augmentationmentioning
confidence: 99%
“…To date, various types of morphological or statistical features manually extracted from ECG signals in the time domain, frequency domain, or nonlinear and transformed domain have generally been used in conventional machine learning classifiers for arrhythmia detection and classification [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Although some of these have shown acceptable performance in several studies, hand-crafted features are difficult to generalize in other situations.…”
Section: Introductionmentioning
confidence: 99%